Potentiating Antibacterial Effect of Locally Deliver Caffeine Nanoparticles on Systemically Used Antibiotics in Periodontal Treatments (Asian Journal of Pharmaceutics (AJP), 2020)
Aims: Subinhibitory concentration of antibiotics at periodontal sites may increase the microbial resistance development; hence, this study was carried out to support the hypothesis that antimicrobial as well as anti-inflammatory action of caffeine and its locally deliver nanoparticles, which can deeply penetrate into the periodontal sites might potentiate and synergize the antibacterial effect of systematically used antibiotics for the treatment of periodontitis. Materials and Methods: In this study, the caffeine-loaded low-molecular-weight chitosan nanoparticles were prepared by ionic gelation methodology. Ex vivo antimicrobial activity of prepared nanoparticles was carried out by periodontitis patient’s stimulated saliva sample. Result: Our finding showed that caffeine nanoparticles in combination with amoxicillin affect the growth of periodontitis microorganisms. Periodontitis microorganism grew on a nutrient agar medium in Petri plates. Agar cups were filled in combination of different concentrations of amoxicillin with or without fixed caffeine concentration containing nanoparticles. High amoxicillin concentration (0.5 μg/ml) with 1 mg of caffeine-containing nanoparticles showed maximum zone of inhibition (1.81 ± 0.24 cm). On the other hand, low amoxicillin concentration (0.3 μg/ml) with 1 mg of caffeine-containing nanoparticles demonstrated significant potentiating inhibitory zone (1.54 ± 0.15 cm) as compare to high amoxicillin concentration (0.5 μg/ml) alone (1.50 ± 0.21 cm). Conclusions: It was shown that caffeine nanoparticles potentiate antibacterial effect of amoxicillin.